Correction: 3D modeling of vector/edge finite element method for multi-ablation technique for large tumor-computational approach. - Gangadhara Boregowda; Panchatcharam Mariappan (PLoS ONE)
[This corrects the article DOI: 10.1371/journal.pone.0289262.].